Social representations of marketing work: advertising workers and social media - Cluley, Robert; Greenhalf, W. (Emerald Group Publishing Limited, 2018)
Purpose: Informed by social representation theory, the study explores how marketing workers represent their activities on social media. Design/methodology/approach: A naturalistic dataset of 17,553 messages posted on Twitter by advertising workers was collected. A sample of over 1,000 unique messages from this dataset, incorporating all external links and images, was analysed inductively using structured thematic analysis. Findings: Advertising workers represent marketing work as a series of fun yet constrained activities involving relationships with clients and colleagues. They engage in cognitive polyphasia by evaluating these productive differences in both a positive and negative light. Research limitations/implications: The study marks a novel use of social representation theory and innovative social media analysis. Further research should explore these relations in greater depth by considering the networks that marketing workers create on social media, and establish how, when and why marketing workers turn to social media in their everyday activities. Practical implications: Marketing workers choose to represent aspects of their work to each other using social media. Marketing managers should support such activities and consider social media as a way to understand the lives and experiences of marketing workers. Originality and value: Marketing researchers have embraced digital media as a route to understanding consumers. This study demonstrates the value of analysing digital media to develop an understanding of marketing work. It sheds new light on the ways marketing workers create social relationships and enables marketing managers to understand and observe the social aspects of effective marketing.